GEOEssential – mainstreaming workflows from data sources to environment policy indicators with essential variables. Issue 2 (1st February 2020) - Lehmann, Anthony; Nativi, Stefano; Mazzetti, Paolo; Maso, Joan; Serral, Ivette; Spengler, Daniel; Niamir, Aidin; McCallum, Ian; Lacroix, Pierre; Patias, Petros; Rodila, Denisa; Ray, Nicolas; et al.
ABSTRACT: When defining indicators on the environment, the use of existing initiatives should be a priority rather than redefining indicators each time. From an Information, Communication and Technology perspective, data interoperability and standardization are critical to improve data access and exchange as promoted by the Group on Earth Observations. GEOEssential is following an end-user driven approach by defining Essential Variables (EVs), as an intermediate value between environmental policy indicators and their appropriate data sources. From international to local scales, environmental policies and indicators are increasingly percolating down from the global to the local agendas. The scientific business processes for the generation of EVs and related indicators can be formalized in workflows specifying the necessary logical steps. To this aim, GEOEssential is developing a Virtual Laboratory the main objective of which is to instantiate conceptual workflows, which are stored in a dedicated knowledge base, generating executable workflows. To interpret and present the relevant outputs/results carried out by the different thematic workflows considered in GEOEssential (i.e. biodiversity, ecosystems, extractives, night light, and food-water-energy nexus), a Dashboard is built as a visual front-end. This is a valuable instrument to track progresses towards environmental policies.